Use of Dual X‐ray Absorptiometry in men with advanced cirrhosis to predict sarcopenia‐associated mortality risk. (25th February 2019) - Sinclair, Marie; Hoermann, Rudolf; Peterson, Adam; Testro, Adam; Angus, Peter W.; Hey, Penelope; Chapman, Brooke; Gow, Paul J.
Abstract: Introduction: Reduced muscle area on CT scan is an independent predictor of mortality in cirrhosis. We examine for the first time the relationship between dual energy x‐ray absorptiometry (DEXA) lean mass parameters on outcomes in cirrhotic men awaiting liver transplantation. Materials and Methods: We retrospectively reviewed DEXA scans performed during transplant assessment between 2001 and 2016. Baseline data including the presence of ascites and MELD score were recorded. DEXA lean mass measures were adjusted for height. The primary outcome was 12‐month wait‐list mortality. Results: Four hundred twenty men with median age 55.4 years [interquartile range 49.2; 59.4] and MELD 16 [12; 20] were studied. Median follow‐up was 58.5 [28.8; 109] months. 12‐month wait‐list mortality was 12.4%. Appendicular lean mass was inversely associated with mortality (HR 0.78 [0.62; 0.98], P  = 0.03). Lean mass of arms (HR 0.37 [0.16; 0.83], P  = 0.02) rather than legs (HR 0.77 [0.58; 1.03], P  = 0.08) was responsible for this association. Upper limb lean mass showed a significant interaction with MELD score in predicting wait‐list mortality, particularly within 4 months. Total lean mass was not associated with mortality but increased in conjunction with increasing ascites (OR for ascites 1.20 [1.15; 1.25], P  < 0.001 for each unit increase in MELD). Conclusion: Upper limb lean mass by DEXA is strongly associated with mortality in men awaiting liver transplantation. The superiority of upper limb lean mass probably relates to confounding of lower limb measures by fluid retention. This DEXA parameter represents a novel and reproducible measure of sarcopenia in cirrhosis.